2021
DOI: 10.1002/cam4.4099
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status on survival in stage III colon cancer patients: A retrospective cohort study using the SEER census‐tract dataset

Abstract: Background The impact of socioeconomic status (SES) has been described for screening and accessing treatment for colon cancer. However, little is known about the “downstream” effect in patients who receive guideline‐concordant treatment. This study assessed the impact of SES on cancer‐specific survival (CSS) and overall survival (OS) for stage III colon cancer patients. Methods The SEER Census Tract‐Level SES Dataset from 2004 to 2015 was used to identify stage III colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(71 reference statements)
1
3
0
1
Order By: Relevance
“…3 Further, we found that Black patients living in low-education (59.4% vs. 67.3%) regions appeared to have lower 5-year survival rates compared to those not living in low-education regions. Compared with findings from other studies, the 5-year survival rate was 72.4% for the lowest SES quintile compared to 78.9% in the highest SES quintile for CRC patients, 23 which is in line with our findings. Associations between neighborhood disadvantage and higher CRC stage at diagnosis and mortality have been found in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…3 Further, we found that Black patients living in low-education (59.4% vs. 67.3%) regions appeared to have lower 5-year survival rates compared to those not living in low-education regions. Compared with findings from other studies, the 5-year survival rate was 72.4% for the lowest SES quintile compared to 78.9% in the highest SES quintile for CRC patients, 23 which is in line with our findings. Associations between neighborhood disadvantage and higher CRC stage at diagnosis and mortality have been found in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…The impact of colonisation globally continues to impact the socioeconomic and health status and life expectancy for Indigenous populations as compared to non-Indigenous populations. Social determinants and lower socioeconomic status have been consistently associated with poor cancer survival [ 44 , 45 ]. In 2006, Anderson et al [ 46 ] alarmingly reported that the life expectancy of Aboriginal and Torres Strait Islander peoples was 20 years lower than that for the total Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…Hastertet al ( 13 ) demonstrated that people living in the lowest socioeconomic status areas had higher colorectal cancer incidence compared to living in the highest socioeconomic status areas. Another study ( 14 ) showed that lower SES was correlated with younger age, Black or Hispanic race/ethnicity, Medicaid/uninsured, and higher T stage. Our results also showed that NSCLC patients with lower SES were associated with young adults, black race, male, squamous carcinoma, upper lobe site and advanced stage.…”
Section: Discussionmentioning
confidence: 99%